Innovations in Community-Based and Interdisciplinary Research: A Network Perspective on Innovation in Social Work Science. (March 2017) - Rice, Eric; Petering, Robin; Stringfellow, Erin; Craddock, Jaih B.
We present a preliminary theory of innovation in social work science. The focus of the piece is two case studies from our work that illustrate the social nature of innovations in the science of social work. This inductive theory focuses on a concept we refer to as transformative innovation, wherein two sets of individuals who possess different expertise and different network connections come together to solve a problem and in so doing transfer ideas from one network and field of expertise to the other. This transfer of ideas inevitably involves the transformation of ideas, such that the final innovation is something new to both groups of people, and as such innovative.